Short Communication: Cross-species amplification of microsatellite markers developed for Jatropha curcas within five species of Jatropha - Darmawan Saptadi; Bambang Heliyanto; Sudarsono Sudarsono (Society for Indonesian Biodiversity, 2020)
Abstract. Saptadi D, Heliyanto B, Sudarsono. 2020. Short Communication: Cross-species amplification of microsatellite markers developed for Jatropha curcas within five species of Jatropha. Biodiversitas 21: 5072-5076. The transferability of SSR markers can be used to access the genetic diversity of related species. There are four close relatives of Jatropha curcas L in Indonesia, which can be utilized as a new diversity source through the interspecific crossing. This research was conducted to determine the ability of cross-species amplification of SSR markers developed from J. curcas to other Jatropha species (J. integerrima, J. multifida, J. gossypifolia, J. podagrica). It also investigated the relationship between these species. Out of 28 primers checked,11 primers showed cross-species amplification in all the species tested. Primer pairs EU099519, EU099528, and EU099525 have no transferability to other species. The overall percentage of polymorphism (PP) among all species tested was 95%, with the mean genetic similarity (GS) was 0.34. Least PP (17.35%) and highest GS (0.60) was found between pairs of J. podagrica and J. multifida. The correlation between the PP with GS was relatively high (0.75). The farthest and closest genetic distance was found between J. curcas/J. gossypifolia and J. podagrica/J. multifida, respectively. Further, selected primers from this study can be utilized in species differentiation, molecular identification of interspecific hybrids, and exploiting the genetic resource.